Prevalence and Factors Predicting Nondiabetic Kidney Disease in Type 2 Diabetic Patients - Vignesh Subramani; Vaishnavi Venkatasubramanian; Jasmine Sethi; Aravind Sekar; Ritambhra Nada; Manish Rathi (Indian Journal of Kidney Diseases)
Background: Renal involvement in type 2 diabetes is mostly presumed to be due to diabetic nephropathy; however, a significant majority of diabetic patients can have pure nondiabetic kidney disease (NDKD) or NDKD superimposed on diabetic kidney disease (DKD). Kidney biopsy cannot be routinely performed for all diabetic patients, and hence, short of conclusive biomarkers, we need to explore various factors that can predict the occurrence of NDKD. Methods: We conducted a retrospective review of all native kidney biopsies conducted in patients with type 2 diabetes at our institute to identify the prevalence and factors that predict NDKD. The demographic data, clinical data, laboratory parameters, and histological results of the patients were obtained from their medical records. Binary logistic regression analysis was performed to evaluate the predictive factors for NDKD. Results: We analyzed a total of 69 patients. The mean (standard deviation) age of the cohort was 51.94 ± 12.7 years and males constituted the majority (68%). Patients with pure DKD, pure NDKD, and NDKD superimposed on DKD constituted 46.3%, 33.3%, and 20%, respectively, of the cohort. Around two-third of pure DKD patients in our cohort had diabetic retinopathy (DR), whereas only around one-fifth (26%) of pure NDKD patients had DR (P = 0.005). Membranous glomerulonephritis (MGN) was the most common histological lesion in the NDKD group (43%), followed by acute tubulointerstitial nephritis (ATIN) (17.3%). Among combined DKD and NDKD, the most common histological diagnosis was pyelonephritis (28.6%), followed by MGN and ATIN (14.3%). Independent factors predicting NDKD were shorter duration of diabetes (odds ratio [OR] = 0.74, confidence interval [CI] =0.59–0.94, P = 0.01) and absence of DR (OR = 0.15, 95% CI = 0.09–0.26, P = 0.01). Conclusion: Kidney biopsy revealed NDKD in nearly half of type 2 diabetes mellitus (T2DM) patients, especially in those with short duration of diabetes and absence of DR. Kidney biopsy is strongly recommended for T2DM patients with atypical presentation and in the absence of DR.